Phragmén-Lindelöf theorem for solutions of elliptic differential equations in a banach space - Gorbachuk, M. L. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
For a second-order elliptic differential equation considered on a semiaxis in a Banach space, we show that if the order of growth of its solution at infinity is not higher than the exponential order, then this solution tends exponentially to zero at infinity.